Insights into Khaldun's Legacy: Ideal Methods in Arabic Language Instruction - Fradana, Heru (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
Ibn Khaldun was a multidimensional Muslim scholar in the 14th century, born in Tunisia, who excelled as a historian, philosopher, sociologist, and economist. His significant work, the "Muqaddimah," provided profound insights into the understanding of history and civilization development. This research delves into Ibn Khaldun's intellectual legacy, specifically focusing on his perceived ideal methods in Arabic language instruction. The research question centers on comprehending the concepts and principles of teaching methods proposed by Ibn Khaldun in the context of Arabic language instruction. The methodology involves analyzing Ibn Khaldun's classical texts and relevant literature to identify elements in his teaching methods. The findings reveal that Ibn Khaldun advocated for a progressive teaching method involving three main phases: delivering material broadly, elucidating the essence of the material, and repeating with emphasis. This concept forms the basis for developing Arabic language teaching strategies that accommodate learners' understanding from a basic level to a more in-depth level. The research's impact encompasses an enhanced understanding of Arabic language teaching methods adaptable to Ibn Khaldun's ideas. The implications involve adjusting curricula and teaching approaches to achieve more effective and holistic learning goals. This research aims to contribute to developing more relevant Arabic language teaching strategies aligned with contemporary educational demands.